Quasiparticle tunneling detection in superconducting qubits - Brunander, Hampus (My University, 2025)
Superconducting quantum circuits are sensitive to decoherence caused by quasiparticle tunneling events, where broken Cooper pairs tunnel across Josephson junctions. While these events typically affect individual qubits, high-energy cosmic ray impacts can generate correlated relaxations and decoherence events across multiple qubits on the same chip, a detrimental problem for quantum error correction protocols that assume independent errors. In this thesis, we studied correlated quasiparticle tunneling using charge-sensitive sensors. The quasiparticle detectors consisted of single-island qubits directly coupled to a waveguide. By recording simultaneous time traces from both quasiparticle detectors, we identified burst events with elevated tunneling rates consistent with cosmic ray impacts. Our correlation analysis found evidence that these high-energy events affect both sensors within the same timeframe, supporting the hypothesis of correlated quasiparticle generation across the chip. The main limitation was relatively low signal-to-noise ratios which affected our ability to distinguish tunneling events from background noise. Additionally, we explored the feasibility of using a conventional transmon qubit as a quasiparticle sensor by exploiting the enhanced charge-sensitivity of higherorder energy transitions. We successfully demonstrated control of the |3⟩ → |4⟩ energy transition, but found that the charge dispersion was below our measurement resolution limit for the device tested, highlighting the need for qubits with lower EJ/EC ratios for this approach.
Keywords: superconducting qubits, quasiparticle tunneling, charge-sensitive sensors, transmon, quantum error correction, cosmic rays, circuit quantum electrodynamics